Studi Pengaruh Sudut Belokan Sungai Terhadap Volume Gerusan - Djufri, Hasdaryatmin (INTEK: Jurnal Penelitian, 2017)
Scouring occurs along the streams and generally increases in their bend areas. This occurence threaten the stability of buildings and facilities built around those areas. This study was conducted by experimental model tests in a laboratory using an artificial channel made of sand with diameter of 0,47 mm and the sand layer density of 1,47 gr/cm3. To assess the effect of river bends on the extent of scours, the water flow was simulated on the artificial channel in 9 times i.e.; 3 variations in the angle of river bends (α) and 3 variations in the flow discharge (Q) for each river bend variation. This study revealed that the volume of scours positively correlated to the angle of river bends. The volume of scours decreased more 20% when the angle of river bends decresed from 60º to 30º. The increase of the flow discharge also enlarged the volume of scours more than 100% at the river bends with small angles